OPTIMIZATION OF TRICHODERMA GROWTH MEDIA FROM TANGKOS WASTE TO IMPROVE VEGETATIVE GROWTH AND CONTROL GANODERMA BONINENSE IN OIL PALM SEEDLINGS - Rizky Randal Cameron; Feriadi; Leni Sabrina; Rifaldo; Muhamad Fathul Nurullah (Universitas Veteran Bangun Nusantara, 2026)
This study evaluated the effectiveness of palm oil empty fruit bunch (EFB)-based growth media inoculated with Trichoderma spp. in enhancing vegetative growth of oil palm seedlings and suppressing Ganoderma boninense. A randomized block design was applied with five treatments: four doses of Trichoderma spp. (2 g, 4 g, 6 g, 8 g) and one untreated control, each repeated eight times. Observed parameters included plant height, stem diameter, leaf number, symptoms of Ganoderma attack, and disease intensity. Results showed that during the first and second months, no symptoms of Ganoderma were detected, consistent with the pathogen’s long latent period. In the third month, initial indications appeared, such as chlorosis of older leaves and necrosis of leaf tips, although no mycelium or necrosis was observed on roots. Vegetative growth analysis revealed variation among treatments. The 4 g and 6 g Trichoderma treatments produced the tallest seedlings, while the 8 g treatment yielded the highest leaf number. Stem diameter remained relatively uniform across treatments and showed no significant differences. ANOVA confirmed that differences among treatments were not statistically significant at the 5% level, though a trend of improved vegetative growth was evident in Trichoderma-treated seedlings. These findings suggest that combining PKEB with Trichoderma spp. has potential as an organic medium and environmentally friendly biocontrol agent against G. boninense. However, effectiveness could not be statistically validated within the three-month observation period. Longer-term studies with more replicates and physiological or molecular assessments are recommended to confirm efficacy and support field application. Keywords: oil palm, Trichoderma spp., EFB, Ganoderma boninense, vegetative growth